2018
DOI: 10.1080/10409289.2018.1544812
|View full text |Cite
|
Sign up to set email alerts
|

Relations of English and Heritage Language Proficiency to Response Inhibition and Attention Shifting in Dual Language Learners in Head Start

Abstract: This study examined the concurrent relations of English (EL) and heritage language (HL) proficiency to executive functions (EF) among low-income dual language learners (DLLs) from immigrant families. In a sample of 90 children (age = 38 to 70 months) from Chinese-speaking Chinese American and Spanish-speaking Mexican American families recruited from Head Start preschools, children’s EL and HL proficiency was assessed using receptive and expressive vocabulary tests, and EF was assessed using behavioral tasks me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…More broadly, and critical to questions of sociocultural specificity, incorporating children's bilingual proficiency and aspects of family SES into the full path model indicated that within-group variations in these sociocultural factors are uniquely associated with variations in their self-regulatory development. The unique associations between children's bilingual proficiency and aspects of their self-regulation are consistent with two previous studies of Chinese American children of immigrant parents (Chen, Hua, et al, 2015;Williams et al, 2019). Together, each of these studies contribute to the growing arguments for examining how withingroup differences in levels of bilingual proficiency e1132 Chen, Deng, Zhang, Wang, and Liu relate to self-regulation (Bialystok, 2017;Sorge, Toplak, & Bialystok, 2017), and underscore the importance of including both bilingualism and family SES as independent predictors of executive function (Krizman, Skoe, & Kraus, 2016).…”
Section: Common and Specific Pathways In Children's Self-regulatory Developmentsupporting
confidence: 90%
See 2 more Smart Citations
“…More broadly, and critical to questions of sociocultural specificity, incorporating children's bilingual proficiency and aspects of family SES into the full path model indicated that within-group variations in these sociocultural factors are uniquely associated with variations in their self-regulatory development. The unique associations between children's bilingual proficiency and aspects of their self-regulation are consistent with two previous studies of Chinese American children of immigrant parents (Chen, Hua, et al, 2015;Williams et al, 2019). Together, each of these studies contribute to the growing arguments for examining how withingroup differences in levels of bilingual proficiency e1132 Chen, Deng, Zhang, Wang, and Liu relate to self-regulation (Bialystok, 2017;Sorge, Toplak, & Bialystok, 2017), and underscore the importance of including both bilingualism and family SES as independent predictors of executive function (Krizman, Skoe, & Kraus, 2016).…”
Section: Common and Specific Pathways In Children's Self-regulatory Developmentsupporting
confidence: 90%
“…While both family SES and multilingualism have been associated with children's self-regulatory development, there is limited evidence for the generalizability of these associations among Asian American youth. For example, while the associations between higher family SES and better executive function in children have been consistently demonstrated across sociocultural groups Obradovi c & Willoughby, 2019), investigations of family SES and selfregulation among immigrant families from any Asian American ethnic group are limited and indicate mixed or nonsignificant associations between family SES, EF, and other indicators of children's self-regulation, such as effortful control and behavioral regulation (Chen, Zhou, Main, & Lee, 2015 ;Chen et al, 2015;Liew, Kwok, Chang, Chang, & Yeh, 2014;Williams, Uchikoshi, Bunge, & Zhou, 2019). Furthermore, while family SES is commonly operationalized as a composite variable of household income and education, previous studies with Chinese immigrant families indicate that income and education level are dissociable aspects of social status that have distinct associations with socioemotional processes (Chen, Zhang, Liu, & Wang, 2020;Chen & Zhou, 2019).…”
Section: Ses Acculturation and Self-regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Immigrant parents may be unable to support the new language due to their own language barriers ( Leyendecker et al, 2018 ). It was found that low-income families use their home language more than the English language with their children ( Williams et al, 2019 ; Haft et al, 2021 ). Therefore, home language input may vary across families for these DLL children.…”
Section: Parental Perceptions Of Bilingualism and Home Language Devel...mentioning
confidence: 99%
“…For example, executive control undergoes a maturation process during the course of adolescence, and demonstrates different kinds of gender differences depending on the specific task (e.g., Malagoli & Usai, 2018 ). Adolescents of later immigrant generations have demonstrated better shifting ability (e.g., Williams et al, 2019 ), and bilingualism can undermine as well as benefit an individual’s executive control (Bialystok, 2011 ; Hilchey & Klein, 2011 ). Therefore, we included adolescents’ self-reported age, gender, nativity (i.e., foreign-born or U.S.-born), and Spanish and English proficiency as covariates in our study.…”
Section: Methodsmentioning
confidence: 99%